Techno-economic assessment of solar technologies to meet hospitals energy needs - Guillem Guerrero; Alba Ramos (International Journal of Applied Power Engineering (IJAPE), 2023)
Hospitals present one of the highest energy consumptions per surface unit, meaning that on-site renewable energy generation and energy efficiency improvements are key to lower hospitals energy demand, external energy dependence and greenhouse gases (GHG) emissions. In this work, the feasibility from the techno-economical point of view of the installation of three solar-based energy generating technologies in hospitals in different climate locations in Europe is addressed. The potential of solar energy technologies to cover the energy needs of the hospitals under study is conducted proposing a novel design and sizing optimization methodology for on-roof installations. The profitability of the different solar-based installations will vary depending on the solar technology output (electrical, thermal or both) and on the type of energy needs of the hospital; but in all cases, profitability is mostly influenced by the price of the current energy source supplying the hospital energy needs. Levelized cost of energy (LCOE) values for on-roof photovoltaic (PV), solar thermal (ST), and photovoltaic-thermal (PV-T) installations obtained are in the range of 0.028-0.056, 0.051-0.096, and 0.053-0.128 €/kWh, respectively; for locations in latitudes from 37 N (Seville) to 60 N (Oslo) in Europe. Results from this work aim to serve as reference for similar studies in a wide range of climates.